2022
DOI: 10.1155/2022/5009512
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of RELL2 as a Potential Biomarker Associated with Tumor Immune Infiltrating Cells in a Pan-Cancer Analysis

Abstract: Background. Receptor expressed in lymphoid tissues-like 2 (RELL2), which is a member of RELT family, is closely associated with the plasma membrane and acts as a modulator for RELT signaling. Overexpression of RELL2 induces the activation of MAPK14/p38 cascade and apoptosis. However, whether RELL2 contributes to cancers remains unclear. Here, we examined its role in cancer patient prognosis and various tumors. Methods. We used several bioinformatics methods, specifically gene set enrichment analysis (GSEA), Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In recent years, the use of immunotherapy as a modern cancer treatment has been expanding in clinical applications 11 . Anticancer immunotherapy has encountered its own opportunities, with several reports identifying biomarkers for immune checkpoint inhibitors (ICIs), such as immune checkpoint gene expression and tumor mutation burden (TMB) 12 . Immunotherapy has rapidly become a cornerstone of many cancer therapies, but the response to immunotherapy has not been very promising, with only some patients showing a durable response to immunotherapy 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of immunotherapy as a modern cancer treatment has been expanding in clinical applications 11 . Anticancer immunotherapy has encountered its own opportunities, with several reports identifying biomarkers for immune checkpoint inhibitors (ICIs), such as immune checkpoint gene expression and tumor mutation burden (TMB) 12 . Immunotherapy has rapidly become a cornerstone of many cancer therapies, but the response to immunotherapy has not been very promising, with only some patients showing a durable response to immunotherapy 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The MSI occurs when some cells perform one or two alleles and a varying number of repeats and has been identified to correlate with clinicopathological features of cancer patients [ 31 ]. The TMB is the number of non-synonymous mutations per coding region of the tumor genome, including the somatic variants per megabase (MB) of the genome, identified by the reported algorithm for the whole exome sequencing [ 32 ]. As shown in Figure 4 , the DMRT3 expression was negatively correlated with the MSI status of DLBC ( p = 0.026), ESCA ( p = 0.023), and READ ( p = 0.013).…”
Section: Resultsmentioning
confidence: 99%
“…Bioinformatic analysis indicates RELL2 expression is a good prognostic indicator for PDAC. Bioinformatic analysis by a separate group confirmed that higher RELL2 expression was correlated with increased survival and better patient outcomes for pancreatic adenocarcinoma (PAAD) [83]. It is important to note that two separate groups report that post-transcriptional modifications of RELL2 nascent RNA modulate the anti-tumorigenic functions of RELL2 in pancreatic [72] and ESCC [67].…”
Section: Pancreatic Cancermentioning
confidence: 98%
“…It is interesting to speculate whether a negative charge introduced by the phosphorylation of RELL1 results in a similar conformation as produced by the N255D mutation, resulting in a pro-tumorigenic form of the protein. In contrast to the upregulation of RELL1 in glioblastoma, bioinformatic analysis indicates that RELL2 is expressed at lower levels in glioblastoma multiforme (GBM) and low-grade gliomas (LGG) versus normal non-malignant tissues [83].…”
Section: Glioma and Glioblastomamentioning
confidence: 99%
See 1 more Smart Citation